Effect of colchicine on Kalanchoe daigremontiana Raym.-Hamet & H.Perrier (Crassulaceae) leaf morphology and stomates (2018)
The current study evaluated the effect of different concentrations and exposure times of colchicine on Kalanchoe daigremontiana leaf morphology and stomates. Initially, K. daigremontiana seedlings were harvested at concentrations of 0.025% and 0.1% (w/v) of colchine and at two exposure times (24 and 48 hours). Subsequently, morphological studies, such as plant height (PH), leaf width (LW), number of leaves (NL), leaf length (LL), leaf thickness (LT) and leaf volume (LV), were done every 15 days for 16 weeks after sowing. Afterwards, the stomates were characterized, taking into account the width, length, stomatal index and number of chloroplasts per stomate. A significant increase in foliar and stomatal morphology was found in treatments with colchicine of 0.025% at 24 and 48 hours. This shows that the use of colchicine achieves greater growth in a short time and increased biomass in medicinal K. daigremontiana plants.